Analisis Faktor Kecemasan Ibu Dalam Pendampingan Anak Belajar Di Rumah - Shanti Rosmaharani; Dian Anisia Widyaningrum (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:   This study aims to determine the factors that influence maternal anxiety in assisting children to study at home / study from home. Methods:   The design of this study used a correlational analytic design with a "cross sectional" approach, with a population of 82 people, and a large sample of 42 respondents. The sampling technique of this research uses Non Probability Sampling: Purposive Sampling. The independent variables are maternal age, child age, education level, and occupation. While the dependent variable is maternal anxiety. Collecting data using an anxiety questionnaire using the ZRAS (Zung Self-Rating Anxiety Scale). The statistical test used  the logistic regression analysisResults: From the results of the logistic regression analysis, it was obtained education level data of 0.0.41 (<0.05) and the most dominant variable for the incidence of dementia in the elderly was a history of hypertension with p value = 0.031 (<0.05) and an OR value of 22.480 that work has a 22,480 times chance of causing anxiety in mothers .Conclusion:  The conclusion of this study is that the level of education and work are related to maternal anxiety. The most dominant factor affecting maternal anxiety is work which can lead to role conflict in mothers. This must be controlled with good emotional management and time management.